Service quality of contact personnel in Turkish capital based hipermarkets in Istanbul - Sayılan, Yosun (My University, 1995)
unknown
Keywords: Genel yönetim; KALİTE-HİZMET KALİTESİ; SÜPERMARKETLER-HİZMET KALİTESİ; Yürütmenin yönetimi